Colton baby conspiracy - Ferrarella, Marie (Colton's of Mustang Valley, 2020)
When a mysterious email threatens her family<U+2019>s corporation, executive Marlowe Colton puts all her energy into protecting Colton Oil. But a more shocking scandal comes in the form of her archrival<U+2014>and one-night lover<U+2014>Bowie Robertson, who uncovers the consequence of their passion. As danger encroaches, Bowie and Marlowe must put aside any bitterness to safeguard the family neither ever expected.